Ethnic migration patterns in South Africa: A case of Zimbabwean immigrants - Zhou, Siyanai (Centre for Actuarial Research (CARE), 2019)
Zimbabwean-born migrants form the largest proportion of the foreign-born population in South Africa; however, relatively little is known about both the international and internal migration behaviour of this population group. This study reviews several migration theories, and existing evidence on Zimbabwean-born migration to South Africa and uses the 2011 Census and 2016 Community Survey data for South Africa to explore both provincial and metropolitan migration patterns of Zimbabwean migrants. The study also seeks to identify characteristics of migrant internal movers and how these are associated with their propensity to migrate. To accomplish this, two modelling approaches are used, namely: the multiplicative component model (TODA) and the logistic regression model. The first modelling approach describes the origin-destination specific migration patterns of this group of migrants. The results from this analytic model show that Zimbabwean migrants are concentrated in three provinces, namely, Gauteng, Western Cape, and Limpopo; particularly in respective metropolitan areas. Also, post-arrival migration is largely focused on these major receiving provinces. The findings suggest that this pattern of concentration is likely to continue. The second modelling approach examines the inter-provincial migration of Zimbabwean migrants. At the aggregate level, the study results show a degree of selectivity of Zimbabwean immigration by factors such as age, sex, marital status, and education. Also, the results show that post-immigration migration is not necessarily significant to migrants’ redistribution. However, for those who move, the logistic regression analysis reveals that province of residence, age, marital status, and sex significantly impact on migrants’ propensity to move from “pioneer settlements” and their effects are consistent over time. Finally, despite concerns about the quality of the data collected in the 2011 census and 2016 Community Survey, our results show that there is general consistency of migration 'patterns’ between the two datasets.